ENHANCING OCCUPATIONAL HEALTH AND SAFETY PRACTICES IN THE MODERN LEMURU FISH PROCESSING INDUSTRY: AN EVALUATION OF THE QUALITY CONTROL UNIT - Nugraha, I Made Aditya; Budiadnyani, I Gusti Ayu; Utari, Siluh Putu Sri Dia; Astiana, Ika; Farida, Iftachul; Juniarta, I Nyoman; Desnanjaya, I Gusti Made Ngurah (Jurnal Perikanan Unram, 2025)
Optimal implementation of Occupational Health and Safety (OHS) is important to create a safe, efficient, and productive work environment. This study examines the implementation of OHS in the modern lemuru fish processing industry. Various integrated strategies are implemented to minimize accident risks, increase productivity, and maintain product quality. Advanced technology approaches such as Internet of Things (IoT)-based monitoring systems, computer-based OHS management systems, and Virtual Reality (VR) technology for training are used. Automation of risky processes with robotics and automatic control technology reduces human involvement in hazardous activities. Data analytics based on machine learning and big data help predict and prevent potential accidents. The results of the study indicate that the integration of appropriate OHS technology and policies improves worker safety, strengthens industry competitiveness, and contributes significantly to long-term success in the modern lemuru fish processing industry.